2020
DOI: 10.1002/ardp.202000214
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new arylazopyrazoles as apoptosis inducers: Candidates to inhibit proliferation of MCF‐7 cells

Abstract: New 4‐arylazo‐3,5‐diamino‐1H‐pyrazole derivatives substituted in the 4‐aryl ring with the acetyl moiety were designed and synthesized. The antiproliferative activity of the novel arylazopyrazoles was examined against the MCF‐7 cell line. Among all target compounds, 8b (IC50 3.0 µM) and 8f (IC50 4.0 µM) displayed higher cytotoxicity as compared with the reference standard imatinib (IC50 7.0 µM). Further studies to explore the mechanism of action were performed on the most active hit of our library, 8b, via anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The cytotoxic properties were evaluated in vitro against human breast cancer cells (MCF-7) and compound 41 (Figure 14) was seen to be the most active (IC 50 of 26.86 mM). In vitro, a kinase assay individuated CDK2/cyclin E as a potential target of the newly synthesised derivatives [93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxic properties were evaluated in vitro against human breast cancer cells (MCF-7) and compound 41 (Figure 14) was seen to be the most active (IC 50 of 26.86 mM). In vitro, a kinase assay individuated CDK2/cyclin E as a potential target of the newly synthesised derivatives [93].…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxic properties were evaluated in vitro against human breast cancer cells (MCF-7) and compound 41 (Figure14) was seen to be the most active (IC50 of 26.86 mM). In vitro, a kinase assay individuated CDK2/cyclin E as a potential target of the newly synthesised derivatives[93].Furthermore, a library of 3,5-diamino-N-aryl-1H-pyrazole-4-carbothioamides was identified as a potential class of HIV-1 inhibitors endowed with innovative mechanisms of action. The aim of the project was to synthesise new chemical entities able to inhibit different viral functions to provide a significant advantage against drug-resistant variants.…”
mentioning
confidence: 99%
“…They displayed the binding energies of −8.90 and −8.60 kcal/mol for 58 and 59, respectively (Ghosh et al, 2021). Ismail et al (2021) synthesized new arylazo-pyrazoles derivatives and used the MTT technique to examine their antiproliferative activity. They observed that two compounds with IC 50 of 3.0 and 4.0 µM displayed higher cytotoxicity compared with the reference standard Imatinib (IC 50 of 7.0 µM).…”
Section: Cell Cycle Cyclin-dependent Kinasesmentioning
confidence: 99%
“…The acetophenone moiety formed more hydrophobic interactions with the amino acids Asp145 and Leu134. After docking studies, they performed ADME analysis by SwissADME, Molsoft, Pre-ADME websites, and DataWarrior software, which also revealed that compound 60 is orally bioavailable (Ismail et al, 2021). 55) and pyrazole-indole hybrids (56, 57) displaying potent CDK2 inhibition.…”
Section: Cell Cycle Cyclin-dependent Kinasesmentioning
confidence: 99%
“…Fig. 1) and as a continuation of our prior work in the eld of the design and synthesis of new anticancer medicines, [19][20][21][22][23][24][25][26] a new series of 6-chloroquinoxaline-3propanamides have been designed as sunitinib's mimetic to optimize pharmacodynamics properties and to overcome certain pharmacokinetic problems demonstrated on sunitinib clinical use such as, BBB permeation and being P-gp substrate.…”
Section: Introductionmentioning
confidence: 99%